Preferensi Mahasiswa dalam Memilih Program Studi Manajemen Universitas Negeri Makassar Melalui Reputasi, Motivasi, dan Biaya Pendidikan - Rahman, Abdul (CV. Lafadz Jaya, 2026)
In the increasingly fierce competition among universities, choosing a study program is a strategic decision influenced by various rational factors. Although numerous studies have been conducted on study program selection behavior, most studies have examined these factors partially, thus not providing a comprehensive picture of the interaction between psychological and economic factors. This study aims to analyze the influence of study program reputation, personal motivation, and tuition fees on students' decisions in choosing the Management Study Program at Makassar State University. This study uses a quantitative approach with a binary logistic regression model, based on data obtained from 100 respondents through a questionnaire. The results show that study program reputation and personal motivation have a positive and significant influence on students' decisions, while tuition fees have a negative and significant influence. The model used has a very good fit with a McFadden R² value of 0.861 and a classification accuracy of 95.3%, indicating high predictive ability. Academically, this study contributes by integrating reputation, motivation, and tuition fees into one empirical logit model, and shows that external factors have a more dominant role than internal factors in determining student decisions. These findings also provide practical implications for study program managers in formulating strategies for improving reputation and more competitive cost policies.